PENEGAKAN HUKUM TERHADAP PEREDARAN KOSMETIK ILEGAL: PERSPEKTIF TEORI KONTROL SOSIAL TRAVIS HIRSCHI - Rastiawaty, Rastiawaty; Alrip, Ismail (Jurnal Legislatif, 2024)
The phenomenon of illegal cosmetics circulation in Indonesia is increasing and is a serious threat to public health. Based on reports from the Food and Drug Supervisory Agency (BPOM), these products often contain hazardous materials and do not have distribution permits, thus endangering consumers. This article aims to analyze law enforcement against the circulation of illegal cosmetics in Indonesia using Travis Hirschi's Social Control Theory. The research method used is normative research using a conceptual and legislative approach used by utilizing the social control theory framework to understand the factors that influence regulatory violations in the distribution of illegal cosmetics. The results of the analysis show that weak social control, such as low social attachment and belief in the law, are dominant factors that allow for rampant violations. The novelty of this study lies in the integration of social control theory into the study of law enforcement, which has not been widely applied in similar studies. The conclusion of this article is that to increase the effectiveness of law enforcement, it is necessary to strengthen regulations, increase public legal awareness, and stricter supervision, especially in the online sector.